1990
DOI: 10.1128/jb.172.3.1392-1399.1990
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the ftsZ gene and cell division in Escherichia coli

Abstract: TheftsZ gene of Escherichia coli, which lies in a cluster of cell division genes at 2 min on the genetic map, codes for a protein which is thought to play a key role in triggering cell division. Using an ftsZ::lacZ operon fusion, we have studied the transcription of the ftsZ gene under conditions in which cell division was either inhibited or synchronized in the bacterial population. InftsZ, ftsA, ftsQ, and ftsl (or pbpB) mutants, there was no change in the differential rate of expression of the ftsZ gene in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
45
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 31 publications
(31 reference statements)
3
45
0
Order By: Relevance
“…In that case, premature termination of DNA synthesis induces the SOS response, which affects the expression of a number of genes. In E. coli, the SOS response leads to an inhibition of cell division by blocking FtsZ activity (51). It has also been observed that flagellar biosynthesis in E. coli is inhibited at nonpermissive temperatures in temperature-sensitive cell division mutants, mediated through flagellar gene transcription (42).…”
Section: Discussionmentioning
confidence: 96%
“…In that case, premature termination of DNA synthesis induces the SOS response, which affects the expression of a number of genes. In E. coli, the SOS response leads to an inhibition of cell division by blocking FtsZ activity (51). It has also been observed that flagellar biosynthesis in E. coli is inhibited at nonpermissive temperatures in temperature-sensitive cell division mutants, mediated through flagellar gene transcription (42).…”
Section: Discussionmentioning
confidence: 96%
“…Other estimates of the relative strength of these promoters, based on studies with transcriptional fusions (Yi et al, 1985;Wang et al, 1991;Flä rdh et al, 1997), found about 60% of the total ftsZ mRNA species started from pZ4-pZ3-pZ2-'pZ1', compared with 92% in our study (Table 4). However, the strength of several of these promoters has been shown to vary considerably with growth rate and with growth phase (Dewar et al, 1989;Aldea et al, 1990;Robin et al, 1990;García-Lara et al, 1996;Flärdh et al, 1997). We therefore suspect that the differences in values found by various groups are likely to result from differences in growth phase.…”
Section: Discussionmentioning
confidence: 99%
“…FtsZ is distributed randomly in the cytoplasm between successive divisions but condenses to form a ring around the cell center at the onset of septation (4). The relative rate of ftsZ expression is inversely correlated with growth rate: when the growth rate decreases, ftsZ expression increases (2,17,38). The ppGpp pool size is also inversely correlated with growth rate (10) minimal medium (33) supplemented with glucose (0.4%), thiamine (10 ,ug/ml), thymine (100 ,ug/ml), and serine, glycine, and methionine (100 ,ug/ml each); relA mutants cannot grow on this medium unless isoleucine and valine (100 ,ug/ml each) are added (49,50).…”
mentioning
confidence: 99%
“…2) shows that all the genes can be transcribed from two promoters located in the ddlB gene, and ftsZ has four additional promoters within the ftsA gene (2,39,40). The expression of ftsZ is inversely correlated with growth rate (2,17,38). The P01 promoter contains a so-called "gearbox" sequence, which is found in other promoters inversely regulated by growth rate (1) and, in one case, has been shown to be essential for this regulation (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation